A developmental approach to bilingual research: The effects of multi-language experience from early infancy to old age. (October 2019) - Filippi, Roberto; D'Souza, Dean; Bright, Peter
Aims and objectives: In this commentary article we consider the benefits of adopting a neuroconstructivist approach in the study of bilingualism in order to promote empirical and theoretical progress on the fiercely debated issue of whether bilingualism confers genuine cognitive advantages. Significance/implications: Although there is a general consensus that exposure to multilingual environments does not impair cognitive development, there are still doubts on the possible beneficial advantages of bilingualism. Critics argue that the evidence for this advantage might have been confounded by unsound or questionable methodological practices. Some investigators have abandoned research in this area, indicating either that there is no bilingual advantage or that it is impossible to capture and therefore rule out alternative explanations for group differences. Rather than dismissing this important theme in the literature, we advocate a more systematic approach in which the effects of multilinguistic experience are assessed and interpreted across well-defined stages of cognitive development. Conclusions: We encourage a broad, developmentally informed approach to plotting the trajectory of interactions between multi-language learning and cognitive development, using a convergence of neuroimaging and behavioural methods, across the whole lifespan. We believe that, through studying infants, children, young adults, adults and the elderly within a coherent and systematic developmental framework, a more accurate and valid account of potential cognitive and neural changes associated with multi-language learning will emerge.